Physical-chemical study of effects of functional groups on adsorption of naphthalene and its derivatives onto high-density polyethylene microplastics - Funari Junior, Ronaldo Antunes (2023)
Microplastics (MP) have received great attention due to the mass-produced residues discharged into the environment. MP are ideal for adhering to organic pollutants that can be easily dispersed, thus posing risks to human health. Furthermore, little has been reported on how different functional groups in polycyclic aromatic hydrocarbons (PAH) derivatives influence the adsorption behavior on MP. To better understand this process, groups methyl (–CH3) and hydroxyl (–OH) were selected and commercial and waste high-density polyethylene (HDPE, ≤ 1mm) were used as adsorbents, and Naphthalene (Nap), 1-Methyl-Naphthalene (Me-Nap) and α-Naphthol as adsorbates. The results showed different behaviors for nonpolar and polar adsorbates. Dispersion forces were the main type of interaction between HDPE and Nap/Me-Nap, while dipole-induced dipole forces and H-bonding were the chief interactions involving MP and polar compounds. Regardless the HDPE source, Nap and Me-Nap have a Type III isotherm, and α-Naphthol presents a Type II isotherm. Nap and Me-Nap fitted to Freundlich isotherm of an unfavorable process ( = 2.12 and 1.11; 1.87 and 1.31, respectively), with positive values of ° (50 and 77.17; 66 and 64.63 kJ mol−1 ) and ° (0.070 and 0.0145; 0.122 and 0.103 kJ mol−1 ) for commercial and waste MP, respectively. Besides, the adsorption isotherm of α-Naphthol on commercial and waste HDPE fitted to the Langmuir model (max = 42.5 and 27.2 µmol g−1 , respectively), presenting negative values of °(−43.71 and −44.10 kJ mol−1 ) and ° (−0.037 and −0.025 kJ mol−1 ). The adsorption kinetic study presents a nonlinear pseudo-second-order model for all cases. The 2 values follow the order Me-Nap > Nap > α-Naphthol in both MP. Therefore, this experimental study provides new insights into the affinity of PAH derivatives for a specific class of MP, helping to understand the environmental fate of residual MP and organic pollutants.